Intracranial germ cell tumour with extra cranial extension in a four month old infant - a case report (Faculty of Medicine Universitas Indonesia, 2005)
Germ cell tumours of the central nervous system infiltrating the ipsilateral extracranial tissues are not a common presentation. A case of intracranial germ cell tumour with extracranial extension in a four month old infant is reported. The patient had undergone excision of the extracranial lesion followed by combination chemotherapy. Twelve months after the completion of the treatment the patient is doing fine and is on regular follow up. (Med J Indones 2005; 14: 179-83)